The Link between Information Technology, Activity-based Costing Implementation and Organizational Performance - Al-Nuaimi, Safaa Ibrahim Mahmood; Mohamed, Rapiah; Alekam, Jamal Mohammed Esmail (International Review of Management and Marketing, 2017)
Activity-Based Costing (ABC) is as a strategic tool that ensures accurate product costs as compared to traditional costing system. The implementation of ABC implementation offers useful information for performance measurement, cost control and strategic decision-making. Meanwhile, certain factors such as Information Technology (IT) determine the success of ABC implementation and its impact on organizational performance. However, past studies in this realm have neither been so emphatic in explaining the role of IT usage in implementing ABC in organizations nor examined the perception of employees and organizations’ decision makers towards the adoption of ABC. In addition, the government of Iraq and the Central Bank of Iraq has also issued strong recommendations to Iraqi banks to consider initiating ABC due to its influence of reduction cost. Thus, this study is motivated to examine the direct and the indirect relationships between information technology, ABC implementation and organizational performance of banks in Iraq. This study surveyed 150 chief accountants of banks in the North region of Iraq. The data collected was analyzed using SPSS version 21. The study revealed that there is a significant relationship between information technology, ABC Implementation and organizational performance. Also, the findings of this study demonstrated that, ABC implementation partially mediates the relationship between information technology, ABC implementation and organization performance. Future researchers are recommended to consider other contingency factors and examine their effect on ABC implementation and organizational performance. Keywords: Organizational Performance, Information Technology, ABC Implementation, Contingency Factors JEL Classifications: M41, M40, M150